Determinants of South Africa’s agri-food export performance: Gravity model approach - Mamashila, Mokgoshi John (Asian Journal of Agriculture and Rural Development, 2024)
The central aim of this study was to investigate the determinants of South Africa's export growth and the challenges associated with agri-food products. To satisfactorily achieve this central aim, two specific objectives were set and addressed differently in this research work. Porter’s Diamond framework was followed to identify factors that influence the export performance of South Africa’s agri-food products, thereby identifying major challenges and opportunities for sustained growth, and the gravity model was applied to examine the main factors influencing South Africa’s agri-food exports to its major trading partners in Africa for the period 1996–2017. The study analyzed and interpreted the results using both primary and secondary data. The study aimed to pinpoint the elements that impact the export performance of South Africa's agri-food products, thereby pinpointing significant obstacles and prospects for long-term expansion. We collected primary data using a structured questionnaire, randomly selecting and interviewing 117 out of 137 respondents. The findings revealed that a scarcity of skilled labor, the expense of skilled labor, the availability of electricity, the cost of raw materials, the cost of advanced technology, transportation expenses, scientific research institutions, pricing, tariffs, language barriers, and crime are the primary barriers to the exportation of agri-food by South African firms. The researcher used 28 countries as export markets to examine factors influencing South Africa's agri-food exports, and the results showed that the size of the economy, geographical proximity, and currency devaluation had a huge effect on exports of agri-food products.